Oesophageal cancer mortality: relationship with alcohol intake and cigarette smoking in Spain. Issue 4 (December 1991) - Cayuela, A; Vioque, J; Bolumar, F
Abstract : STUDY OBJECTIVE–The aim of the study was to explore temporal changes in mortality from oesophageal cancer that could be related to tobacco and alcohol consumption. DESIGN–The study used mortality trends from oesophageal cancer over the period 1951-1985. In addition, available trends on per capita consumption of alcohol and cigarettes are also presented. SETTING–Data for this study were derived from Spain's National Institute for Statistics. MAIN RESULTS–Age standardised mortality rates from oesophageal cancer have increased significantly among men in Spain from 1951 to 1985 (p less than 0.01). Mortality rates in women have not changed significantly during the same period, although there is evidence of a certain decrease in recent years. Trends of per capita cigarette consumption from 1957 to 1982 related positively with oesophageal cancer mortality among men, whereas no significant relationship was observed in women. Trends of beer, spirits, and total alcohol consumption were also positively correlated with oesophageal cancer mortality in men. Among women, a weaker relationship was found. Wine consumption showed no relationship with oesophageal cancer mortality either in men or women. CONCLUSIONS–These results are similar to those found in other studies, supporting a role of alcohol (spirits and beer) and cigarette consumption in causation of oesophageal cancer. No relationship was observed with wine consumption.